Generalized Quasilinearization Method for a Class of Semilinear Elliptic Systems (Journal of Partial Differential Equations, 2020)
In this paper, the method of generalized quasilinearization is extended to a class of semilinear elliptic systems, and the sequences which are the solutions of linear differential equations that converge to the unique solution of the given semilinear elliptic system are obtained.
Keywords: semilinear elliptic systems; boundary value problem; generalized quasilinearization